Efektivitas Pelaksanaan Perjanjian Pra Nikah Terhadap Harta Bersama - Puspa Maria Hukum; Ali Azhar; Vivi Arfiani Siregar (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2026)
Marriage constitutes a physical and spiritual bond between a man and a woman that gives rise to legal consequences not only for their personal relationship but also for the property acquired during the marriage, commonly referred to as joint marital property. To prevent the commingling of assets and potential property disputes in the future—particularly in cases of divorce or the death of one of the parties—the law provides prospective spouses with the opportunity to enter into a prenuptial agreement (marriage agreement) as regulated under Article 29 of Law Number 1 of 1974 concerning Marriage. This study aims to examine and analyze the effectiveness of the implementation of prenuptial agreements in regulating joint marital property, as well as to identify the factors influencing the effectiveness of such implementation within society. This research employs an empirical juridical method with statutory, conceptual, and sociological approaches, and is descriptive-analytical in nature. Data were obtained through library research and descriptive-analytical in nature. Data were obtained through library research and interviews with relevant parties, and were subsequently analyzed qualitatively. The findings indicate that, in practice, the implementation of prenuptial agreements has not been fully effective, due to several factors, including the public's limited understanding of the functions and benefits of prenuptial agreements, prevailing cultural perceptions that such agreements reflect a lack of trust between spouses, and limited outreach conducted by relevant institutions such as notaries and religious affairs offices. Nevertheless, for couples who have executed and registered a prenuptial agreement, the agreement has proven effective in providing legal certainty and protecting each party's assets, particularly in the in practice, the implementation of prenuptial agreements has not been fully effective, due to several factors, including the public's limited understanding of the functions and benefits of prenuptial agreements, prevailing cultural perceptions that such agreements reflect a lack of trust between spouses, and limited outreach conducted by relevant institutions such as notaries and religious affairs offices. Nevertheless, for couples who have executed and registered a prenuptial agreement, the agreement has proven effective in providing legal certainty and protecting each party's assets, particularly in the event of divorce. This study recommends the need for enhanced legal outreach and education to raise public awareness of the importance of prenuptial agreements as a legal instrument to ensure certainty and legal protection over joint marital property in marriage.